Survey on patients' attitude towards the nutritional counselling in the dental setting - M. Iriti; G. Spallino; R. Franchini; M. Rigoni; P. Muti; G. Lodi; A. Sardella; E. M. Varoni (Nature Publishing Group, 2024)
Abstract Aim A healthy diet could help to prevent both oral and systemic diseases, with dentists and nutritionists supplementing their skills. The dental setting, where patients periodically refer to seeking oral health care, represents a powerful opportunity for nutritional counselling. To the best of our knowledge, no study is available on patients' attitudes towards dietary counselling in the dental setting. This cross-sectional study investigates patients' attitude towards receiving nutritional support within the dental setting and it elucidates whether a transdisciplinary approach would be well accepted. Materials and Methods A questionnaire was administered to patients attending three different clinics: a private clinic, a hospital dental clinic of the national healthcare system and the private dental practice within the same hospital. Results Three hundred thirteen questionnaires were collected. Most dental patients acknowledged receiving nutritional advice from both dentists and nutritionists. The nutritionist within the dental setting was positively perceived, providing useful advice to prevent oral and systemic diseases and also drawing up a diet with periodic follow-ups. Discussion and conclusion These findings support the positive attitude of patients towards receiving nutritional counselling within the dental setting. The dental clinics can be pivotal in oral and systemic disease screening and prevention and a multidisciplinary approach is highly encouraged.